Examining The Moderating Factor of Perceived Price in Between Employee Performance and Consumer Satisfaction at Grand Inna Hotel Medan - Shu, Efin; Chianata, Finny (Institut Pariwisata dan Bisnis Internasional, 2024)
Consumer satisfaction is one key determinant of the success of a business. The ratings and feedback given by guests about employees at Grand Inna Hotel Medan mostly indicate that employee performance have not met guest expectations, and guests are dissatisfied. This study aims to evaluate the moderating factor of price perception in between employee performance and consumer satisfaction. This research uses the quantitative method. Data collection was done by distributing questionnaires. The population is all customers of Grand Inna Hotel Medan, with total sample of 96 people that were determined using the Lemeshow formula. The data is analyzed using SPSS statistical software. The findings indicate that employee performance has a significant influence on consumer satisfaction, and price perception negatively moderates the variables. To enhance the perception of appropriate pricing among customers, Grand Inna Hotel Medan needs to consider more transparent pricing strategies and provide value commensurate with the services offered.